Making the Link between HRM and Sustainable Development: A Case for University Sector in KSA - Albaqami, Adi Sudan (Journal of Ecohumanism, 2025)
This paper discusses the relationship between human resource management (HRM) and sustainable development as well as examines how HRM strategies can serve as an opportunity for university sector in KSA to achieve sustainable development across all its dimensions including economic, social, technical and environmental. To achieve these objectives, a theoretical framework was developed for examining HRM and sustainable development. A set of hypotheses was extracted from theoretical framework. To validate hypotheses, primary data were collected through a questionnaire that administered with 40 specialists and experts as well as 15 deans of faculties of business administration in Saudi universities. Then data were then analysed using SPSS. The Results showed that there was a strong link between HRM and sustainable development. Also, HRM strategies had a large effect on sustainable development dimensions (economic, social, technical and environmental). The researcher recommends that priority should be given to investment in human capabilities and skills through the adoption of appropriate HRM strategies that improve HR performance and enable universities to achieve long-term sustainable development.